2010
DOI: 10.1097/scs.0b013e3181cf603a
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Total Lower Lip Defects Using Radial Forearm Free Flap With Subsequent Tongue Flap

Abstract: Subtotal and total reconstruction of the lower lip is a challenge for the plastic surgeon. Large defects extending to the chin area can be difficult to manage with only local flaps, and free flaps are better suited. In an attempt to restore the lower lip with the vermilion, the authors used the radial forearm free flap with anteriorly based ventral tongue flap in 5 patients. The tongue flap is used 3 months after the free flap procedure, and this flap is divided 3 weeks later. The tongue flap transfer, adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 4 publications
0
17
0
4
Order By: Relevance
“…The reconstructive choice for lip defect was according to the defect size and area. Yildirim et al 12 reported that defects larger than 30% but smaller than 80% of the lower lip can be reconstructed with local flaps (e.g., advanced oral mucosal flaps, 5,6 extended lip flaps, 13,14 tongue flaps, or V-Y advancement flap 15 ). However, if the defect includes more than 80% of the lower lip, successful reconstruction is difficult because all of these methods allow only a static suspension of the reconstructed lip to the oral commissure.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The reconstructive choice for lip defect was according to the defect size and area. Yildirim et al 12 reported that defects larger than 30% but smaller than 80% of the lower lip can be reconstructed with local flaps (e.g., advanced oral mucosal flaps, 5,6 extended lip flaps, 13,14 tongue flaps, or V-Y advancement flap 15 ). However, if the defect includes more than 80% of the lower lip, successful reconstruction is difficult because all of these methods allow only a static suspension of the reconstructed lip to the oral commissure.…”
Section: Discussionmentioning
confidence: 98%
“…There are few reports of reconstructing complete lip defects in the literature. 4,7,8 For repairing partial lip defects, a free RFA flap 5,6,9 has been the most frequently reported. It has the advantage of a good blood supply, but only a straight axial vessel is acquirable, which does not provide adequate coverage of the upper and lower lips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is also well established and reported by many authors. [6][7][8][9][10][11][12][13] Sakai et al 2 sutured the tendon to the orbicularis oris muscle and dermis in the nasolabial region to suspend the reconstruction. Other surgeons have reported good outcomes by suturing the tendon to the periosteum of the malar eminence or to the orbicularis muscle of the upper lip near the philtral columns.…”
Section: Discussionmentioning
confidence: 99%
“…Several modifications fixing the tendon to the masseter muscle, the modiolus, or the orbicularis oris muscle around the philtral columns have been demonstrated. [5][6][7][8][9][10][11][12][13] Use of fascia lata grafts and anterolateral thigh flaps for large lower lip defects has also been reported, with good outcomes. 14 Despite advances in reconstruction surgery, patients still experience many sequelae after extensive surgery, including poor aesthetic appearance and functional disturbances such as dysphagia and impaired speech and drooling.…”
mentioning
confidence: 94%